Civil Registration as a guarantee of the human right to identity and family - Manso, Mariana (2017)
The definition of a universal ‘civil registry’ (a.k.a vital statistics office) - coined in modernity - establishes that this is the basis for States to have accurate information of their populations and thus to be able to elaborate their social and economic development plans.  The relationship among people, family, and ‘civil registry’ is intimate and permanent, people are born, coexist, marry, and die and all these are “civil” and “family” facts - acts recorded with the Civil Registry. The family and the filial bonds must receive special protection from the government bodies and, especially, the ‘civil registry’ which is a fundamental link in the protection of people’s identity, intangibility of bodies, and diversity.